Pengembangan Sistem Informasi Pengolahan Data Guru Dan Pegawai Pada Sma Negeri 1 Mamuju Sulawesi Barat Berbasis Website - Asya, Erma; Nuraini; Yeni, Hari (Jurnal Ilmu Ekonomi dan Bisnis, 2026)
The processing of teacher and staff data at SMA Negeri 1 Mamuju is still carried out manually using spreadsheet applications and physical documents, resulting in problems such as data duplication, slow search processes, and the risk of document loss. This study aims to develop a website-based information system to manage teacher and staff data so that administrative processes become more effective and efficient. The method used is the Web Development Life Cycle (WDLC), which includes the stages of requirements analysis, system design, development, testing, and implementation. The results show that the developed information system is able to speed up the data search process by up to 78%, reduce data redundancy, and improve the accuracy of staff data input. Testing using the Black Box Testing method indicates that all system features function according to user requirements. Therefore, this website-based information system can serve as an effective solution to support personnel data management at SMA Negeri 1 Mamuju.